Mobile Environment as a Factor in the Digitalization of Trade - Ćuzović, Sreten; Sokolov-Mladenović, Svetlana; Veljković, Jelena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The time we live in, in many things in particular is unique and inspiring. Times like these significantly change living and business conditions. Combining the power of GPS systems, the ubiquity of mobile devices and the creativity of network marketing, at a time when customers are becoming more sophisticated, the endeavor to permanently develop a mobile technology device at the company level becomes inevitable. There is a need to move from an conversative approach to designing a trading strategy to that of an appropriate online environment. Trade, if it is given adequate momentum and a meaningful strategic framework, can be considered as determinant of a country's progress. M-commerce on the other hand creates a range of opportunities for businesses from different sectors by utilizing innovative services, applications and information content, thereby projecting significant growth prospects. In this regard, the subject of research in this paper is the positioning of mobile commerce in the digital economy. Derived from the subject, the aim of the paper is to give an overview of the current state and trends of m-commerce, to identify its key variables and business models. The expected result is an understanding of the achieved level of development of m-commerce in Serbia and the world, as well as the development perspectives of innovative value-added solutions that use commercial advantages of mobility, viewed in the context of improving the business practices of our companies.